1998
DOI: 10.1016/s0035-9203(98)90811-2
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of oral-fluid collection devices for the determination of rubella antibody status in a rural Ethiopian community

Abstract: We compared 3 different oral-fluid collection devices to assess their suitability for use in community studies of rubella antibody. Of 58 individuals enrolled from 13 households from a southern Ethiopian village, 38 provided a blood sample and oral fluids by the 3 devices: 2 proprietary, Omni-SAL and OraSure, and a third a polystyrene sponge swab (Sponge). The Sponge swab, used like a toothbrush, was most acceptable to survey staff and to participants of all ages, although it proved ill-adapted for fluid extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 12 publications
2
27
0
Order By: Relevance
“…Oral fluid testing simplifies the diagnostic process in specific populations in which drawing blood is difficult and dangerous. As previously demonstrated in other studies, the number of oral fluid collections in all sites confirmed the general acceptability of the study by MSM in outreach settings [16,24]. In our study, an info-pack containing a condom, a lubricant and information about STD prevention and screening centres available in the area was given to respondents in order to facilitate the enrolment and to promote safer sex and testing practice, during the data collection.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Oral fluid testing simplifies the diagnostic process in specific populations in which drawing blood is difficult and dangerous. As previously demonstrated in other studies, the number of oral fluid collections in all sites confirmed the general acceptability of the study by MSM in outreach settings [16,24]. In our study, an info-pack containing a condom, a lubricant and information about STD prevention and screening centres available in the area was given to respondents in order to facilitate the enrolment and to promote safer sex and testing practice, during the data collection.…”
Section: Discussionsupporting
confidence: 87%
“…The method used was consistent with the approach adopted in previous studies [15][16][17][18][19][20][21]. In the TLS, spaces (or locations) are venues attended by the target population; times refer to specific days and time periods when the target population congregates in each space.…”
Section: Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of including the 'weak positive ' component is demonstrated by the greatly improved fit over a model with just positive and negative components. The increase with age in the proportion of positives in the 'weak positive ' component, particularly noticeable after age 15 years, reflects the decay of rubella specific antibody levels in persons infected many years previously as observed in other studies [4][5][6][7]. The approach of using strong and weak positive components to introduce flexibility into the infected distribution worked well in this study because the distribution of results for the uninfected population did not change with age (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…Oral fluid was collected using a well-evaluated (10, 19) sponge device (Oracol; Malvern Medical Development, Worcester, United Kingdom) that was rubbed firmly along the gums for 1 min. Extraction and storage methods are detailed elsewhere (11,21). Ethical approval for this study was provided by the Kenya National Ethical Review Committee and the Coventry Research Ethics Committee, Coventry, United Kingdom.…”
Section: Methodsmentioning
confidence: 99%